2013
DOI: 10.1371/journal.pone.0067284
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exposure to Electromagnetic Fields from High Voltage Transmission Lines and Neurobehavioral Function in Children

Abstract: BackgroundEvidence for a possible causal relationship between exposure to electromagnetic fields (EMF) emitted by high voltage transmission (HVT) lines and neurobehavioral dysfunction in children is insufficient. The present study aims to investigate the association between EMF exposure from HVT lines and neurobehavioral function in children.MethodsTwo primary schools were chosen based on monitoring data of ambient electromagnetic radiation. A cross-sectional study with 437 children (9 to 13 years old) was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(41 reference statements)
1
17
2
Order By: Relevance
“…They were within the range of mean values reported in Europe [26] and similar to those recorded in a primary school in northern Spain [11]. However, they were higher than levels recently described by Huang et al in two primary schools in Guangzhou, China [27].…”
Section: Discussionsupporting
confidence: 88%
“…They were within the range of mean values reported in Europe [26] and similar to those recorded in a primary school in northern Spain [11]. However, they were higher than levels recently described by Huang et al in two primary schools in Guangzhou, China [27].…”
Section: Discussionsupporting
confidence: 88%
“…Since that time, the negative effects of ELF-EMF was adopted and extensively researched. Epidemiological investigations identified that ELF-EMF exposure can cause the total decline of sleep quality[ 20 ], and some neurological symptoms, such as depression, anxiety, fatigue, and memory decline[ 21 ]. In addition, some reports have suggested the potential association between ELF-EMF and AD.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure levels of ELF-MFs detected in this study could affect children’s perception [ 27 ] and is associated with a higher risk of childhood leukemia [ 13 , 14 , 15 , 16 ]. Disorders of cognitive function [ 17 , 18 , 19 ], disorders of memory performance, headaches, and sleep disorders [ 20 , 21 ] are also associated with these exposure levels. Although there has been no explicit evidence for adverse health effects in children by ELF-MFs exposure, since the nervous and immune systems of children could be more sensitive to ELF-MFs [ 2 , 28 ], children should avoid exposure to ELF-MFs as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The association between exposure to ELF-MFs and the risk of childhood cancer has been extensively investigated in epidemiological studies [ 13 , 14 , 15 , 16 ]. Studies on disorders of cognitive function [ 17 , 18 , 19 ], disorders of memory performance, headaches, and sleep disorders [ 20 , 21 ] in relation to EMFs have also been conducted.…”
Section: Introductionmentioning
confidence: 99%